COMMUNICATION TECHNIQUE OF HIZBUT TAHRIR INDONESIA (HTI) IN THE DEVELOPMENT OF CADRE IN NORTH SUMATERA - Rubino Rubino Rubino; Mohd. Hatta Hatta; Abdullah Abdullah Abdullah (State Islamic University of North Sumatra Indonesia, 2017)
This study aimed to analyze the communication techniques applied Hizbut Tahrir Indonesia (HTI) in the development of cadres in North Sumatra. The approach used in this research is qualitative approach, with reason to understand the problem in its natural setting, and interpret this phenomenon based on the meaning given by the informant, also because this research is multidimensional which is the result of various situation complexity, so it needs to be analyzed the context around it . The informant of this research is determined by purposive technique that is explored based on the purpose of this research, with informant plan amounted to 6 (six) people that is 1 (one) management and 5 (five) person responsible lajnah. Based on the data obtained, the results of this study are, there are three communication techniques applied by the HTI in cadre development activities are: (1) informative techniques, namely by providing information about HTI and the main ideas it develops, to all levels of society both students , students, scholars, intellectuals, as well as influential figures in society such as government leaders, legislators, leaders of mass organizations, leaders of political parties, etc., as well as members of the cadre at the general level of learning, general level, (2) persuasive techniques by inviting them to join and support HTI preaching through dialogue, discussion, bulletin sharing, magazines, etc., and (3) the technique of human relationships by giving advice inter-personal to the community or members experiencing problems through consultation activities Key Words: Communication Technique, Hizbut Tahrir Indonesia, The Development of Cadre.